Ответ:
Пошаговое объяснение:
1
f'(x)=3x²-2
f'(x)=3*1²-2=1
2
f'(x)=2x-6
2x-6=0
2x=6
x=6:2
x=3
f(2)=2²-6*2+9=1 наибольшее
f(3)=3²-6*3+9=0 наименьшее
f(4)=4²-6*4+9=1 наибольшее
3
С₄²=
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1
f'(x)=3x²-2
f'(x)=3*1²-2=1
2
f'(x)=2x-6
2x-6=0
2x=6
x=6:2
x=3
f(2)=2²-6*2+9=1 наибольшее
f(3)=3²-6*3+9=0 наименьшее
f(4)=4²-6*4+9=1 наибольшее
3
С₄²=![\frac{4!}{2!2!} =\frac{4*3*2!}{2!*2*1} =6 \frac{4!}{2!2!} =\frac{4*3*2!}{2!*2*1} =6](https://tex.z-dn.net/?f=%5Cfrac%7B4%21%7D%7B2%212%21%7D%20%3D%5Cfrac%7B4%2A3%2A2%21%7D%7B2%21%2A2%2A1%7D%20%3D6)